Science’s reproducibility and replicability crisis: International business is not immune - Aguinis, Herman; Cascio, Wayne F.; Ramani, Ravi S. (Journal of International Business Studies, 2017)
International business is not immune to science’s reproducibility and replicability crisis. We argue that this crisis is not entirely surprising given the methodological practices that enhance systematic capitalization on chance. This occurs when researchers search for a maximally predictive statistical model based on a particular dataset and engage in several trial-and-error steps that are rarely disclosed in published articles. We describe systematic capitalization on chance, distinguish it from unsystematic capitalization on chance, address five common practices that capitalize on chance, and offer actionable strategies to minimize the capitalization on chance and improve the reproducibility and replicability of future IB research.